Ridge Pattern Representation for Fingerprint Indexing - Uysal, M.; Gorgunoglu, S. (Elektronika ir Elektrotechnika, 2014)
Fingerprint is a widely used distinguishing biometric characteristic and indexing has an important role in fingerprint identification for large databases. A method to represent ridge pattern is proposed for fingerprint indexing. Ridge pattern within a triangular area is represented by a numerical value, which is suitable to use as an index and very robust to elastic distortion. Experimental results are promising. The proposed representation method can be utilized to further narrow down the search space of databases by the other indexing methods, especially the ones based on minutiae triplets. DOI: http://dx.doi.org/10.5755/j01.eee.20.7.8026